A Note on Reducing Subspaces of Toeplitz Operator on the Weighted Analytic Function Spaces of the Bidisk Hw2D2 - Hongzhao Lin (Journal of Function Spaces)
We discussed the reducing subspaces of Toeplitz operators Tz1Nz2M  N≠M on the weighted analytic function spaces of bidisk Hw2(D2). The result shows that if the weight w is of type-I, the structure of reducing subspaces of Tz1Nz2M  N≠M on Hw2D2 is very simple.